Targeting H3N2 Influenza Virus RNA-dependent RNA Polymerase by Using Bioactives from Essential Oils from Eucalyptus polybrachtea, Cymbopogon citratus and Cymbopogon khasianus - Sharma, Arun Dev; Kaur, Inderjeet (Biology, Medicine, & Natural Product Chemistry, 2023)
A dramatic surge of H3N2 influenza virus is of grave concern worldwide and particularly in India. H3N2 cause acute respiratory infection, however, a few drugs are available for its mitigation. Subsequently, researchers have been involved in efforts to discover novel antiviral mechanisms that can lay the basis for new anti-influenza drugs. Influenza virus RNA-dependent RNA polymerase (RdRP) is a multi-functional hetero-trimer, implicated in the production of viral mRNA, hence plays a major role in viral infectivity thus directly associated with survival of the virus. RdRP have been cited as anappropriate target for therapeutic drug design. In the present study molecular docking was designed to estimate the effect of potent bioactive moleculesfrom essential oils from Eucalyptus polybrachtea (eucalyptus oil, EO), Cymbopogon citratus (lemon grass essential oil, LEO) and Cymbopogon khasianus (palmarosa essential oil, PEO) against RdRP protein. GC-FID (gas chromatography with flame-ionization detection) based composition profile, and in-silico docking study was conducted by using CB-dock 2 analysis followed by 2D interactions. GC-FID revealed eucalyptol, geranial and geraniolas major phytocompounds in EO, LEO and PEO respectively. The docking score indicated effective binding of ligands to RdRP. Interactions results indicated that, RdRP/ligand complexes form hydrogen, van der waals forces, pi-alkyl, alkyl, and pi-Sigma interactions. Based on above findings of aroma profile and docking, therefore, it was recommended that essential oils from above mentioned aromatic cropsmay represent potential herbal treatment to mitigate H3N2 infections.